Macroscopic examination of fetal appendices in delivery room: good practice at Panzi hospital - D., Boengandi Walala; O., Nyakio Ngeleza; B., Mukanire Ntakwinja; K., Raha Maroyi; G., Katenga Bosunga; D., Mukwege Mukengere (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The review of fetal appendices is described in the literature, and its importance is well established. Indeed, pathological findings in the placenta can provide information on the pathogenesis of the fetus, including intrauterine growth retardation, mental retardation or neurodevelopmental disorders. This helps to understand a child's disability, but also maternal complications such as preeclampsia. Despite the relevant information provided by the various studies, fetal appendices are not systematically examined in several maternity hospitals in our country, DR Congo. We report good practice from the examination of fetal appendices to the maternity ward of Panzi Hospital, in the town of Bukavu, South Kivu, DR Congo.